Assessing AI Integration in Islamic Higher Education: A Mixed-Methods Fishbone Diagram Analysis - Aan Ansori; Damyati, Fitri; Dhestyani, Syifa Amara (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2024)
The integration of Artificial Intelligence in higher education has shown significant potential to improve the efficiency and effectiveness of learning. The strategic implementation of AI in Indonesian State Islamic Higher Education Institutions fosters innovative pedagogy and improved academic performance. This study employs the Fishbone Diagram approach to systematically analyze Artificial Intelligence's impact on Indonesian State Islamic Higher Education Institutions education, identifying key factors influencing implementation. The method employs a reverse-cause analysis, mapping factors contributing to a primary issue, and identifying underlying causes and sub-factors. Findings highlight the crucial roles of technological infrastructure, human resource readiness, supportive policies, adaptive curriculum design, and organizational culture. This study underscores the necessity of integrated AI adoption frameworks in Indonesian Islamic higher education, harmonizing technological advancement with Islamic pedagogical principles. This study offers a foundational framework guiding Indonesian State Islamic Higher Education Institutions in developing sustainable and ethical AI policies. Comprehensive AI policies and strategies are essential for PTKIN to harmonize innovation with Islamic principles.